Conservation of passively dispersed organisms in the context of habitat degradation and destruction. Issue 2 (11th December 2014) - Teller, Brittany J.; Miller, Adam D.; Shea, Katriona; Cadotte, Marc
Summary Passively dispersed species, such as many plant species, rely on abiotic forces to achieve movement. Despite the fact that such species form the base of many terrestrial and oceanic food webs, these species are often overlooked by conservation management plans because it is assumed that they are dispersed easily and widely, and therefore are relatively unthreatened by anthropogenic influences in comparison with poorly dispersing species. To quantify the threat presented by habitat degradation and destruction to passively dispersed species, we present a theoretical population model of passively dispersed organisms that incorporates the effects of increased dispersal‐associated mortality. We examine how the effects of habitat degradation and destruction depend on species' dispersal tactics, specifically: highly dispersive, highly retentive or spatially biased. Contrary to prevailing intuition, highly dispersive species may suffer the strongest absolute negative demographic effects in the face of changes in human‐modified landscapes. These results suggest that passively dispersed organisms may be more threatened by landscape modification than previously thought, and should be more carefully considered in plans for conservation and management. Synthesis and applications. Since passively dispersed species cannot choose their ultimate settling location, they are therefore less likely to arrive at suitable habitat in landscapes that are degraded or destroyed. If we do not understand the implications for population dynamics of demographic costs of dispersal in fragmented landscapes, we may fail to predict declines of apparently widespread species, including many wind‐dispersed plants and insects, benthic invertebrates and airborne microbes. Conservation and management plans should consider loss of propagules to unsuitable habitat for highly dispersive as well as poorly dispersive species, to avoid potential errors.